The internationalization of internal conflicts : threatening the state - Freedman, Amy L. (Routledge, 2014)
This project looks at the international dimension to internal conflicts and asks: under what conditions do domestic conflicts become opportunities for regional or global actors to become involved? Why have some countries been able to successfully deal with this problem while others have not?